Stenogramy III Dumy Państwowej jako źródło do badań nad polityką zagraniczną Rosji w latach 1907-1912 - Budziński, Janusz R. (Acta Universitatis Lodziensis. Folia Historica, 1998)
To aim of article is an attempt to answer a question, whether they can be regarded as a good source of information to investigate Russia’s foreign policy in these years. The introduction conteins a short history of Russian parliamentarism from the beginning of the 20th century. Special attention is given to elections to the 3rd Duma and its party com position. Next, taken each session into account, the meetings are presented, when Russian foreign policy was discused. Then, the speeches of ministers of foreign affairs Aleksander Izwolski and his successor Sergiusz Sazonow are analized. Also, the speeches of deputies are considered in which they were presenting their attitude to information given to them by ministers of foreign affairs. The conclusion contains opinions on usefulness of the shorthands as a source to investigate Russian foreign policy. They seem to be a valuable material, but they requise completion with other documents. They present the main directions of Russian foreign policy, but they lack a discussion of concrete interstate treaties. Some repercussions only can be found in the speeches of deputies. Thanks to these speeches it is possible to determine the opinions of parties seated in the Duma.